Conjoined twins with a single heart with complex disease - Pabis, Julia Simões; Ribeiro, Paulo Victor Zattar; Schulze, Milena Luisa; Benvinuti, Júlia de Novaes; Ribeiro, Paulo André; Pabis, Francisco Cesar (ARCHIVES OF HEALTH INVESTIGATION, 2020)
Conjoined twins are a rare presentation with an estimated incidence of 1: 50000 pregnancies. They occur due to a random event, not related to heredity, maternal age or delivery conditions. This article is a case-report of a pair of female thoraco-omphalopagus conjoined twins, who were diagnosed during prenatal period through a morphological ultrasound. After a 24-week gestation period, the female newborns had a total weight of 1100g, and were born of a cesarean section. Both fetuses scored 3 in the Apgar scale in the first minute, getting down to a score of 1 in the fifth minute. Soon after birth, the newborns were referred to the Intensive Care Unit, where supportive measures were taken and transthoracic Doppler echocardiography was performed for diagnostic confirmation. The echocardiogram showed that there was only one heart for both newborns with a complex heart disease. In 75% of the cases of thoraco-omphalopagus conjoined twins, structural heart disfigurements are found in at least one of the fetuses. Besides, in approximately 80-90% of the cases, the cardiac abnormalities in the heart junction are far too complex, making it impossible to surgically separate the fetuses. This way, a structural and functional analysis of the heart is considerably more efficient post-birth, and it’s shown to be more accurately done through an echocardiography. This reveals that cardiac changes are a crucial factor in the fetal and postnatal evaluations of conjoined twins. Such procedures are a way of providing adequate medical recommendations, which may always be honest and based on scientific evidence. Descriptors: Diseases in Twins; Twins, Conjoined; Heart Diseases. References McMahon CJ, Spencer R. Congenital heart defects in conjoined twins: outcome after surgical separation of thoracopagus. Pediatr Cardiol. 2006;27(1):1-12 Rode H, Fieggen AG, Brown RA, Cywes S, Davies MRQ, Hewitson JP et al. Four decades of conjoined twins at Red Cross Children’s Hospital–lessons learned. S Afr Med J. 2006; 96(9Pt2):931-40. Barth RA, Filly RA, Goldberg JD, Moore P, Silverman NH. Conjoined twins: prenatal diagnosis and assessment of associated malformations [published correction appears in Radiology 1991 Jan;178(1):287]. Radiology. 1990;177(1):201-7. Spencer R. Anatomic description of conjoined twins: a plea for standardized terminology. J Pediatr Surg. 1996;31(7):941-944. Andrews RE, Yates RW, Sullivan ID. The management of conjoined twins: Cardiology assessment. Semin Pediatr Surg. 2015;24(5):217-20. Andrews RE, McMahon CJ, Yates RW, et al. Echocardiographic assessment of conjoined twins. Heart. 2006;92(3):382-87. Lopes LM, Brizot ML, Schultz R, Liao AW, Krebs VLJ, Francisco RPV et al. Twenty-five years of fetal echocardiography in conjoined twins: lessons learned. J Am Soc Echocardiogr. 2013;26(5):530-538. Brooks R. Ian McEwan attacks church over right to die. Sunday may 18 2014. The Sunday Times https://www.thetimes.co.uk/article/mcewan-attacks-church-over-right-to-die-gq8nwtbhqjb. Sih DA, Bimerew M, Modeste RRM. Coping strategies of mothers with preterm babies admitted in a public hospital in Cape Town. Curationis. 2019;42(1):e1-8. Albuquerque S, Pereira M, Fonseca A, Canavarro MC. Impacto familiar e ajustamento de pais de crianças com diagnóstico de anomalia congênita: influência dos determinantes da criança. Rev psiquiatr clín. 2012;39(4):136-41. Pereira PK, Lima LA, Legay LF, Santos JFC, Lovisi GM. Congenital malformation of the baby and risk of maternal mental disorders during the pregnancy-puerperal period: a systematic review. Cad Saúde Colet (Rio de Janeiro). 2011;19(1):2-10.